Tanshinone IIA decreases the levels of inflammation induced by Aβ1–42 in brain tissues of Alzheimer's disease model rats. Issue 12 (17th August 2016) - Lu, Bei-Ling; Li, Jian; Zhou, Jun; Li, Wen-Wen; Wu, Heng-Fei
Abstract : To study the pathogenesis of Alzheimer's disease (AD) and explore the possible anti-inflammatory mechanism of tanshinone IIA (TanIIA), we evaluated the quantity of neurons and the expression levels of interleukin-1β (IL-1β), IL-6, glial fibrillary acidic protein, CD11b, C1q, C3c, and C3d in brain tissues of AD rats treated with TanIIA. Thirty male Sprague–Dawley rats were randomized into three groups: sham group, TanIIA treatment group, and Aβ1–42 group. Aβ1–42 treatment was performed by injecting Aβ into the hippocampus of rats and then tagged position. Brain tissue morphological structure has been observed with HE staining and the staining of exogenously injected Aβ1–42 was observed by immunohistochemistry, which confirms the success of the Aβ1–42 group. After TanIIA treatment, levels of IL-1β, IL-6, glial fibrillary acidic protein, CD11b, C1q, C3c, and C3d were measured in paraffinized brain tissue sections from all groups by immunohistochemistry staining. The results showed that no 6E10 was detected in the control group, and the difference in the expression levels of 6E10 between the Aβ1–42 group and the TanIIA treatment group was not significant ( P >0.05), suggesting that both the Aβ1–42 group and the TanIIA treatment group received the same amount of Aβ. The Aβ1–42 group showed a significant increase in the expression levels of inflammatory markers compared with the sham group ( P <0.05) and the TanIIA treatment group showed a partial improvement in reducing inflammation. Therefore, Aβ triggered brain inflammation and activated the complement system. TanIIA treatment reduced the number of astrocytes and microglial cells, and induced a partial decrease in complement molecules in the brain of AD rats. These findings suggested that TanIIA may represent a potential therapeutic treatment in neurodegenerative diseases such as AD to support the survival of neurons by reducing expression levels of inflammatory factors.